The Role of MicroRNA and Microbiota in Depression and Anxiety - Rosa, Julia M.; Formolo, Douglas A.; Yu, Jiasui; Lee, Thomas H.; Yau, Suk-yu (Frontiers in Behavioral Neuroscience, 2022)
Depression and anxiety are devastating disorders. Understanding the mechanisms that underlie the development of depression and anxiety can provide new hints on novel treatments and preventive strategies. Here, we summarize the latest findings reporting the novel roles of gut microbiota and microRNAs (miRNAs) in the pathophysiology of depression and anxiety. The crosstalk between gut microbiota and the brain has been reported to contribute to these pathologies. It is currently known that some miRNAs can regulate bacterial growth and gene transcription while also modulate the gut microbiota composition, suggesting the importance of miRNAs in gut and brain health. Treatment and prevention strategies for neuropsychiatric diseases, such as physical exercise, diet, and probiotics, can modulate the gut microbiota composition and miRNAs expressions. Nonetheless, there are critical questions to be addressed to understand further the mechanisms involved in the interaction between the gut microbiota and miRNAs in the brain. This review summarizes the recent findings of the potential roles of microbiota and miRNA on the neuropathology of depression and anxiety, and its potential as treatment strategies.